Beyond the Douai‐Reims Bible: The Changing Publishing Strategies of the Kellam Family in Seventeenth‐Century Douai. (8th September 2021) - Soetaert, Alexander; Wyffels, Heleen
Abstract: The career of the Catholic Englishman Laurence Kellam is often reduced to his most impressive edition, the Old Testament of the Douay-Rheims Bible (1609–1610), an English Catholic Bible translation edited by the English College of Douai. Yet, there has been scarce attention for the remaining 190 editions, printed in English, as well as in Latin, French and Dutch, that bear a Kellam imprint. The discovery of another fifty editions that should be ascribed to the Kellam press demands a reappraisal of its activities and significance. By analysing both printed and archival sources, this article intends to fit the Bible edition of 1609–1610, and English Catholic printing on the continent more generally, into the wider perspective of three generations of publishing activities and family history, highlighting the increasingly tight connections between several generations of the Kellam family and the authors, institutions, and fellow-publishers of their host society.